KH. Nashiruddin Qodir dan Pesantren Darut Tauhid Al Hasaniyah Tuban 1988-2017 - Evi Eviyanti (Qurthuba: The Journal of History and Islamic Civilization, 2018)
Abstract: This article examines Nashiruddin Qodir's role in the dynamics of Islamic education in Tuban, especially as the founder and caretaker of the Darut Tauhid Islamic boarding school. The problems discussed in this thesis are: (1) How is the biography of KH. Nashiruddin Qodir, (2) What is the history of the Darut Tauhid Al Hasaniyyah Islamic Boarding School in 1988-2017, (3) What is the role of KH. Nashiruddin in developing the Darut Tauhid Al Hasaniyyah Islamic boarding school. Writing this article using historical research methods which consist of several, namely: (1) Heuristics (2) Verification (3) Interpretation (4) Historiography. The approach used in this thesis is a historical descriptive approach. The theory used in this study is the theory of Continuity and Change by Jhon Obert Voll, role theory by Biddle and Thomas, and leadership theory by Max Weber. In this study it can be concluded that (1) KH. Nashiruddin Qodir was born in Tuban on July 1, 1949 to H. Abdul Qodir and Hj. Suwaedah. KH. Nasiruddin is married to Hj. Siti Khoiriyah and was blessed with seven children. KH. Nashiruddin once studied at the MIS Sarang Islamic boarding school. (2) The Darut Tauhid Al Hasaniyyah Islamic Boarding School was founded in 1988. The development of the Darut Tauhid Al Hasaniyyah Islamic Boarding School was very rapid starting from the facilities and infrastructure, educational institutions, and the number of students. (3) The role played by KH. Nashiruddin Qodir in developing the Darut Tauhid Al Hasaniyyah Islamic boarding school was as a fund collector, in the social and religious fields, as well as the initiator of the establishment of Ma'had Aly Al Hasaniyyah. Keywords: biography, pesantren, role